2013
DOI: 10.1021/es401919k
|View full text |Cite
|
Sign up to set email alerts
|

Triclosan Exposure Increases Triclosan Resistance and Influences Taxonomic Composition of Benthic Bacterial Communities

Abstract: Triclosan (TCS) is a broad-spectrum antimicrobial compound that is incorporated into numerous consumer products. TCS has been detected in aquatic ecosystems across the U.S., raising concern about its potential ecological effects. We conducted a field survey and an artificial stream experiment to assess effects of TCS on benthic bacterial communities. Field sampling indicated that TCS concentrations in stream sediments increased with degree of urbanization. There was significant correlation between sediment TCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
114
7
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(136 citation statements)
references
References 109 publications
(217 reference statements)
10
114
7
5
Order By: Relevance
“…4) might be bacterial species that can utilize TCS as carbon source. Drury et al (2013) reported that TCS exposure could trigger increasing TCS resistance with benthic bacteria and decreased benthic bacterial diversity. The similarity coefficient in UPGMA clustering among treatments and control basically declined with the increase of TCS concentrations in the sediments, indicating that the effects of TCS on bacterial community increased with TCS concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…4) might be bacterial species that can utilize TCS as carbon source. Drury et al (2013) reported that TCS exposure could trigger increasing TCS resistance with benthic bacteria and decreased benthic bacterial diversity. The similarity coefficient in UPGMA clustering among treatments and control basically declined with the increase of TCS concentrations in the sediments, indicating that the effects of TCS on bacterial community increased with TCS concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…187 Furthermore, recent studies suggest that triclosan exposure can lead to resistance, particularly for Pseudomonas aeruginosa. 164,165 Finally, a 2014 study found that the presence of triclosan in the nasal cavities of healthy adults was associated with S. aureus nasal colonization, suggesting that the impact of triclosan on the microbiome is potentially important and warrants further investigation. 166 …”
Section: Methods For Hand Hygiene Adherence Measurementmentioning
confidence: 99%
“…The 96-h half maximal effective concentration (EC50) and 96-h no observed effect concentration (NOEC) for Scenedesmus were 1.4 and 0.69 μg L −1 , respectively, and the 96-h median lethal concentration (LC50) for Pimephales promelas and Lepomis macrochirus were 260 and 370 μg L −1 , respectively (Orvos et al 2002). Exposure to TCS might increase antimicrobial resistance and lead to crossresistance to antibiotics (Drury et al 2013;Schweizer 2001). TCS can significantly elevate the vitellogenin mRNA expression of mature male western mosquitofish, suggesting that TCS has the potential to act as an endocrine disruptor (Raut and Angus 2010).…”
Section: Introductionmentioning
confidence: 99%